Case report: Thymoid differentiated carcinoma of thyroid: Two cases - Zhao, Yanjie; Liu, Jiafeng (Frontiers in Surgery, 2023)
Department of Thyroid and Hernia,Gannan Medical University,Ganzhou,Jiangxi Thymoid thyroid carcinoma is a rare thyroid tumor, which is often reported as a case. Two cases of thymoid thyroid carcinoma are described in this paper.